Spare Some Change?: The Policing of Shelter-Resistant Homeless in Missoula, Montana - Coolidge, Jacob Daniel (2012)
Homelessness rates in the United States have continually increased over the past thirty years. The financial crisis of 2008 has created a ripple effect of unemployment, foreclosures, and an increased presence of homelessness in cities across the country. This increased presence of homelessness has created challenges for service providers and local governments across the country. Many cities, including New York, Los Angeles, and San Francisco have implanted “Quality of Life” ordinances that criminalize certain facets of homeless life. Missoula, Montana has not been impervious to this trend and has a unique labor market that exaggerates the presence of poverty. In 2009, the City of Missoula passed two such ordinances designed to combat crime associated with homeless persons in the downtown corridor; the ordinances outlaw aggressive solicitation and pedestrian interference. The primary offenders have been the downtown shelter-resistant homeless. My research investigates the pragmatic application of these two “Quality of Life” ordinances in Missoula Montana. What are the outcomes of the interactions between law enforcement and the homeless? What factors determine what kinds of outcomes police and service providers utilize? In order to answer these questions, I employed qualitative research methods, specifically participant-observation and in-depth interviews. I observed at a local emergency homeless shelter, three community meetings, and as a member of a homeless outreach team. I documented my observations and experiences in ethnographic field notes. In addition, I interviewed professional stakeholders representing the Downtown Business Improvement District and the Missoula Police Department. In my research, I found that there were four possible outcomes of interactions between police or service providers and the shelter-resistant homeless: negotiation, informal resolution, formal resolution, and incarceration. Furthermore, there are four significant factors in determining outcome, including (1) Nature of Offense (2) Visibility (3) “Fatigue” and (4) Cooperativeness. The findings reflect the unique relationship between the Business Improvement District and the downtown officer, as well as the impact of national policing philosophies behind “Quality of Life” ordinances on the shelter-resistant homeless population